Higher education reforms: Latin America in comparative perspective - Bernasconi, Andrés; Celis, Sergio (Education Policy Analysis Archives, 2017)
This article introduces a special issue of EPAA/AAPE devoted to recent higher education reforms in Latin America. The last two decades have seen much policy development in higher education in the region, examined and discussed by scholars in each country, but dialog with the international literature on higher education reform, or an explicit comparative focus, have been mostly absent from these works. By way of presentation of the papers included in this issue, we first provide an overview of major policy changes in higher education in the Latin American region since the 1990s. We then turn to the six works in this special issue to describe the theories and methods supporting them. Next, we illustrate how general analytic categories can be derived from single or multi country case studies to illuminate themes capable of cutting across the particulars of national contexts, with their unique traditions, policy paths, and politics. Our three common threads are, first, the types of drivers for reform, that is, how policy change originates, either bottom-up from the institutions, or top-down from the government, and various possibilities in between. Second, understanding challenges to institutional autonomy in a continuum of intensity of state intended intervention in higher education. Third, explaining different levels of strain between public and private sectors in higher education based on conditions of competition for economic resources. While the papers in this special issue do not cover all countries, nor all issues on which policy has been crafted in the last two decades across the region, the collection of articles herein account for topics of enduring importance: faculty work in Ecuador, financial aid in Colombia, public policy decentralization in Argentina, quality assurance models in Colombia and Uruguay, the emerge of new institutions and universities in Argentina and Uruguay, and social justice, access, and inclusion in higher education, in Argentina, Bolivia, Brazil, Chile, Colombia, and Ecuador. The articles presented in this special issue provide much insight onto higher education policy in Latin America and, additionally, offer ample opportunity to develop social science knowledge on the basis of strong comparative work.